Item Analysis of Final Examination Questions for Social Studies in Junior High Schools through the ITEMAN Program - Wahab, Abdul; Hasibuan, Annim; Siregar, Roswani; Risnawaty; Ningsih, Tri Zahra (Journal of Education Reseach and Evaluation, 2023)
The analysis of the quality of the test items is very important because it will affect the results of the test itself. The problem is that teachers often do not analyze test items, so the test results do not accurately describe the potential of students. For this reason, this study aims to analyze the items on the semester final exam for social studies class VII. This type of research is a quantitative description. The research sample was the answer sheets of Class VII students from public middle schools, totaling 119 sheets. The research instrument consisted of end-of-semester exam question sheets, student answer sheets, and a scoring rubric. The research data was obtained from student answer sheets, which were collected after the semester final exams for social studies took place. The data analysis technique uses statistical analysis through the ITEMAN program. The results of the study place the validity and reliability of the instrument in the high category. The results of the analysis of the difficulty level of the items and the differential power showed that there was an imbalance in the composition of the test items. So it was concluded that the test questions for the end of semester exams for social studies subjects in junior high school needed to be reviewed. The results of this study are expected to have implications for teachers in making social studies test questions in the future as well as input for the government in making policies, especially in the field of education.